2017
DOI: 10.2119/molmed.2016.00139
|View full text |Cite
|
Sign up to set email alerts
|

miR-155 Modifies Inflammation, Endothelial Activation and Blood-Brain Barrier Dysfunction in Cerebral Malaria

Abstract: miR-155 has been shown to participate in host response to infection and neuroinflammation via negative regulation of blood-brain barrier (BBB) integrity and T cell function. We hypothesized that miR-155 may contribute to the pathogenesis of cerebral malaria (CM). To test this hypothesis, we used a genetic approach to modulate miR-155 expression in an experimental model of cerebral malaria (ECM). In addition, an engineered endothelialized microvessel system and serum samples from Ugandan children with CM were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 58 publications
1
49
0
Order By: Relevance
“…MiR‐155, identified as an oncogenic miRNA, is the product of B‐cell integration cluster gene. Previous studies indicate that miR‐155 may be involved in human atherosclerotic plaques and miR‐155 may be overexpressed in monocytes, macrophages, human coronary artery endothelial cells, and human mesangial cells after treatment with LPS, TNFα, or interferon‐γ . According to our results, LPS could promote miR‐155 expression in HUVECs, which is consistent with those studies.…”
Section: Discussionsupporting
confidence: 92%
“…MiR‐155, identified as an oncogenic miRNA, is the product of B‐cell integration cluster gene. Previous studies indicate that miR‐155 may be involved in human atherosclerotic plaques and miR‐155 may be overexpressed in monocytes, macrophages, human coronary artery endothelial cells, and human mesangial cells after treatment with LPS, TNFα, or interferon‐γ . According to our results, LPS could promote miR‐155 expression in HUVECs, which is consistent with those studies.…”
Section: Discussionsupporting
confidence: 92%
“…From a literature search of the PubMed database, we found 62 microRNAs related to immunological and inflammatory responses, cytoadhesion, and neuronal apoptosis (Figure and Supporting Information Table ). Among them, three microRNAs (microRNA‐146a, microRNA‐27a, and microRNA‐155) were related to each of these mechanisms (Barker et al., ). Subsequent miRSNP database searching indicated that the SNP in microRNA‐155 (rs200351615 A>G) has a minor allele frequency of 0.001, too low to reliably detect in the sample size of our study.…”
Section: Discussionmentioning
confidence: 99%
“…13) Increasing reports have suggested that miR-155 is closely involved in the regulation of cell apoptosis, immunity, inflammation, and bloodbrain barrier. [14][15][16] In this study, we suspected that miR-155 might play a vital role in the effect of PNS on the ischemic injury-related inflammation. We first investigated the effect of PNS on the proliferation of SH-SY5Y cells.…”
Section: Introductionmentioning
confidence: 89%